PERSUASIVE COMMUNICATION STRATEGIES IN ENVIRONMENTAL CAMPAIGNS: A COMPARATIVE STUDY OF THE BODY SHOP INDONESIA AND ECOTON FOUNDATION - Iqbal, Muhamad Iqbal; Prasetyo, Kurniawan (Universitas Mercu Buana, 2025)
Indonesia is currently facing an unprecedented waste management emergency, with annual production reaching 69.7 million tons. This research provides a comprehensive analysis of the persuasive communication strategies utilized by two prominent yet distinct actors: The Body Shop Indonesia (commercial) and Ecoton Foundation (non-commercial). By employing a qualitative case study methodology, this study dissects digital narratives, symbolic messaging, and community engagement frameworks across multiple social media ecosystems. The findings reveal a dichotomy in persuasive approaches; The Body Shop employs